Placenta Accreta Spectrum in delivered women is associated with history of curettage: A case-control study at Dr. Moewardi General Hospital, Surakarta, Indonesia - Prabowo, Helena Adelia; Anggraini, Nutria Widya Purna; Anggraeni, Asih; Setyawan, Sigit (Universitas Airlangga, 2025)
HIGHLIGHTS Placenta Accreta Spectrum cases rise in proportion to the high frequency of uterine wall damage. A significant association was found between curettage history and Placenta Accreta Spectrum. ABSTRACT Objective: Placenta Accreta Spectrum (PAS) involves abnormal placental adherence to the myometrium, causing severe obstetric hemorrhage and increased maternal morbidity and mortality (3,000–5,000 mL blood loss). Its global incidence has risen from 0.12% to 0.31%, linked to uterine trauma from cesarean sections or curettage. This study evaluates the association between curettage history and PAS. Materials and Methods: This study employed an analytical observational design with a case-control approach. Purposive sampling was utilized, resulting in the inclusion of 134 participants who met the predefined criteria. The study population consisted of women who delivered and were referred to Dr. Moewardi General Hospital, Surakarta, Indonesia, between May 2022 and May 2024. Data were analyzed using IBM SPSS version 25. The Chi-square test was applied to assess the association between variables at a significance level of p < 0.05, while logistic regression analysis was conducted to identify the most influential variables. Results: The study cohort comprised 67 patients diagnosed with PAS and 67 without PAS. A statistically significant association was observed between a history of curettage and PAS, as determined by the Chi-square test, with a p-value of 0.000. Logistic regression analysis further confirmed this association, yielding a p-value of 0.001 and an odds ratio (OR) of 5.769 (95% CI: 2.090–15.928) for a history of curettage. Conclusion: A history of curettage is significantly associated with the development of PAS. Patients with a prior curettage procedure are 5.769 times more likely to develop PAS compared to those without such a history.